An update on the clinical diagnostic value of β-hCG and αFP for intracranial germ cell tumors. Issue 1 (December 2016) - Hu, Mingming; Guan, Hongzhi; Lau, Ching; Terashima, Keita; Jin, Zimeng; Cui, Liying; Wang, Yuzhou; Li, Guilin; Yao, Yong; Guo, Yi; Li, Yan; Zhong, Dingrong; et al.
Abstract Background Pathological examination combined with tumor markers has become a standard for the diagnosis of intracranial germ cell tumors (ICGCTs), but the current concept of 'secreting germ cell tumors' and three empirically highly specific diagnostic criteria (β-hCG ≥ 50 IU/L or αFP ≥ 10 ng/mL; β-hCG ≥ 100 IU/L or αFP ≥ 50 ng/mL; β-hCG > 50 IU/L or αFP > 25 ng/mL) are not based upon pathology examination or CSF cytology. Further investigation is needed to re-evaluate their value. Methods A multidisciplinary diagnostic team was created. Valid β-hCG/αFP data were collected from cases of ICGCTs confirmed by pathology and CSF cytology (n = 58) between 1991 and 2012, and from suspected ICGCTs cases (n = 17) between 2011 and 2012 as controls [Langerhans cell histiocytosis (LCH), n = 12; and other intracranial tumor (ICT), n = 5]. The cut-off points for β-hCG and αFP were calculated using receiver operating characteristic (ROC) curves. Results This study clarifies the relative rationality of one criteria (β-hCG > 50 IU/L and αFP > 25 ng/mL); confirms new β-hCG diagnostic cut-off points: CSF β-hCG ≥ 8.2 IU/L and serum β-hCG ≥ 2.5 IU/L (sensitivity of 47 and 34 %, respectively, specificity of 100 %, both;P < 0.05); and empirically adjusts the criteria for αFP to ≥ 3.8 ng/mL in CSF and to ≥ 25 ng/mL in serum. The total diagnostic sensitivity for ICGCTs finally increased from 34.6 to 65.4 % (P < 0.05, diagnostic value of CSF β-hCG exceeds 90 %). Subtype diagnosis improved with αFP in 16.7 % of non-geminomatous germ cell tumor cases. Conclusion New evidence-based criteria of β-hCG and αFP can help improving early and formal diagnosis of ICGCTs, and is of great clinical significance.